Eccrine spiradenoma: a rare adnexal tumour with atypical presentation, a case report - Adnan Salim; Muhammad Usman Tariq; Sana Zeeshan (Journal of the Pakistan Medical Association, 2020)
Abstract First described in 1934, eccrine spiradenoma (ES) is a rare, benign adnexal tumour arising from eccrine sweat glands. It commonly presents as a slow-growing nodule on the upper trunk, and head and neck region, mostly in the age bracket of 15-35 years, with no gender preference. While no established guidelines exist for optimal management of malignant ES, some therapies have been studied. The diagnosis of this entity is extremely important as it can harbour a malignant component with disastrous outcomes which may be missed due to its strong resemblance to benign lesions, such as a papilloma. Here, we present the case of a 35-year-old lady who presented with a papilloma-like growth on the upper medial aspect of the thigh which was diagnosed as eccrine spiradenoma upon excision. Keywords: Eccrine Spiradenoma, adnexal tumour, dermal lesion, case report. Continuous...